Psychometric properties of the Chinese version of the quality of nursing care scale among hospital nurses: a bifactor exploratory structural equation modeling analysis - Chiu-Shu Fang; Cheng-Hsien Li; Shu-Ching Ma; Fang-Ming Hwang; Maria Manuela Martins; Fan-Hao Chou (BMC Nursing)
Abstract Background Nurses play an indispensable role in healthcare teams. The quality of nursing care reflects nurses’ ability to integrate care and their overall performance in patient care, making it a core objective of clinical nursing. The Chinese version of the Quality of Nursing Care (QNC) scale is a multidimensional assessment tool used for self-evaluation of nursing care quality and holds significant importance in clinical practice. This study aimed to assess the reliability and validity of the Chinese version of the QNC scale among nurses. Methods This was an observational, cross-sectional, methodological study conducted at three hospitals in southern Taiwan. The 25-item Chinese version of the QNC scale was employed in the study. Data were collected from 944 nurses (response rate: 65.42%) through an online survey conducted between July and August 2022. The factor structure of the QNC scale was evaluated using confirmatory factor analysis (unidimensional, independent cluster model, higher-order, and bifactor) and first-order, higher-order, and bifactor ESEM. Model comparisons were conducted to determine the best-fitting factor structure. Results The bifactor ESEM provided the best fit for the QNC scale, consisting of a general QNC factor and seven specific factors: patient satisfaction, health promotion, complication prevention, well-being and self-care, functional readaptation, nursing care organization, and responsibility and rigor. Some items exhibited significant cross-loadings, highlighting the model’s ability to capture the multidimensional nature of nursing care quality. Conclusions The bifactor ESEM model demonstrated the best model fit for the Chinese version of the QNC scale, offering a reliable and interpretable representation of the multidimensional nature of nursing care. The validated scale provides a valuable tool for assessing nursing care quality in clinical practice.